МОРАЛЬНИЙ ВИМІР ЛЮДСЬКОЇ СУТНОСТІ З ПОГЛЯДУ СВЯЩЕНИКА (Педагогіка вищої та середньої школи, 2008)
In this article orthodox priest A. Harmash’s point of view on the problem of moral establishment of modern man and the influence of system of education is analysed.